Helmut Hasse und Emmy Noether: die Korrespondenz 1925 - 1935 - Hasse, Helmut; Noether, Emmy (Univ.-Verl. Göttingen, 2006)
This book reproduces the complete extant correspondence between Emmy Noether and Helmut Hasse. There are 82 such letters, of which 79 are from Noether to Hasse, dating from 1925 until Noether's sudden death in 1935. The correspondence reflects a crucial period in the development of 20th century algebra and number theory, in particular class field theory. Details of proofs appear alongside with conjectures and speculations. Also discussed are questions of textbook presentation, e.g., of Galois theory. Aside from mathematical details, the spontaneity of Noether's style allows many glimpses at the image that Emmy Noether and Helmut Hasse had of the topics they were working in. The Hasse - Noether correspondence is a rich source for those who are interested in the rise and the development of mathematical notions and ideas. Each letter is accompanied by a detailed commentary supplied by the editors. For the convenience of the reader, numerous cross-references, extended indexes, and short biographies of all persons mentioned in the correspondence have been added.
Auch als elektronisches Dokument vorhanden
Literaturverz. S. 249 - 266. - Enth. Briefsammlungen von Helmut Hasse und Emmy Noether
Keywords: Hasse, Helmut -- 1898-1979 -- Correspondence; Noether, Emmy -- 1882-1935 -- Correspondence; Bibliografie; Briefsammlung; Noether, Emmy; Hasse, Helmut